Operational characteristics of internal public transportation in the UP Diliman campus - Abisado, Kimko Christine L.; Castañeda, Amante M. Jr (College of Engineering, University of the Philippines Diliman, 2017)
The main purpose of this study is to describe operating and financial performance of UP Ikot and Toki and develop a database of information which will be useful in planning and restructuring of internal public transport system in UP Diliman campus. The development of readily available data describing operational characteristics of Ikot and Toki were obtained by analyzing figures based from transport surveys namely - Drivers' Interview Survey, On-Board Survey, Boarding and Alighting Survey and Operators' Interview Survey. Results from the Mega Manila Transport survey was used as a benchmark for comparison from the measured operational and financial characteristics of Ikot and Toki and significant variations were observed which shows the following (1) UP Ikot has the highest number of round trips and highest boundary fee amounting at an average of 25 and PhP 800, respectively, than the other two route categories; (2) gross revenue of drivers at PhP2,138 from MMPTS' data are higher than the two internal UP route categories; (3) Toki's route are the lengthiest at 8.05 km compared to the other two and; (4) drivers' take home pay amounting at PhP 464 from MMPTS shows lesser amount than Ikot and Toki's PhP 1308 and PhP750, respectively. From these findings, it can be observed that number of roundtrips decreases as route length increases and that the gross revenue and drivers' take home pay increases with the number of roundtrips.